Prophet Yunus and big fish - Khan,saniyasnain (china goodwordbooks, 2021)
The story of Prophet Yunus (Jonah) and the big fish, as told by Saniyasnain Khan, is a popular Islamic children's book that introduces young readers to a key Quranic narrative. The book focuses on the story of Prophet Yunus, who was swallowed by a large fish after disobeying God's command and leaving his people before they had fully embraced Islam. Inside the fish's belly, Prophet Yunus repents and prays to God, who then saves him. The story emphasizes themes of repentance, forgiveness, and the power of prayer.